Natural HLA-B*2705 Protein Ligands with Glutamine as Anchor Motif: IMPLICATIONS FOR HLA-B27 ASSOCIATION WITH SPONDYLOARTHROPATHY - Infantes, Susana (American Society for Biochemistry and Molecular Biology, 2013)
The presentation of short viral peptide antigens by human leukocyte antigen (HLA) class I molecules on cell surfaces is a key step in the activation of cytotoxic T lymphocytes, which mediate the killing of pathogen-infected cells or initiate autoimmune tissue damage. HLA-B27 is a well known class I molecule that is used to study both facets of the cellular immune response. Using mass spectrometry analysis of complex HLA-bound peptide pools isolated from large amounts of HLA-B*2705(+) cells, we identified 200 naturally processed HLA-B*2705 ligands. Our analyses revealed that a change in the position (P) 2 anchor motif was detected in the 3% of HLA-B*2705 ligands identified. B*2705 class I molecules were able to bind these six GlnP2 peptides, which showed significant homology to pathogenic bacterial sequences, with a broad range of affinities. One of these ligands was able to bind with distinct conformations to HLA-B27 subtypes differentially associated with ankylosing spondylitis. These conformational differences could be sufficient to initiate autoimmune damage in patients with ankylosing spondylitis-associated subtypes. Therefore, these kinds of peptides (short, with GlnP2, and similar low affinity to all HLA-B27 subtypes tested but with unlike conformations in differentially ankylosing spondylitis-associated subtypes) must not be excluded from future researches involving potential arthritogenic peptides.